The origins of American religious nationalism - Haselby, Sam (Religion in America, 2015)
The powers of the earth : secularism and American nationalism -- "The songs of a nation" : the Connecticut wits and the new English empire -- To raise a holy people, wear no slouched hat : the Methodist settlement of the frontier -- Sovereignty and salvation on the frontier of the early republic -- "The love of order and righteous laws" : early national liberals and the missions movement -- "A complete chain of communication" : religious literature and Protestant nation-building -- A monster and the wandering savage : the resolution of frontier revivalism and national evangelism